Answer:
The first first five terms of this sequence are
Step-by-step explanation:
[tex]a(n) = 27(0.1)^{n - 1} [/tex]
where n is the number of term
For the first term
n = 1
[tex]a(1) = 27(0.1)^{1 - 1} = 27(0.1) ^{0} [/tex]
= 27(1)
Second term
n = 2
[tex]a(2) = 27(0.1)^{2 - 1} = 27(0.1)^{1} [/tex]
= 27(0.1)
Third term
n = 3
[tex]a(3) = 27(0.1)^{3 - 1} = 27(0.1)^{2} [/tex]
Fourth term
n = 4
[tex]a(4) = 27(0.1)^{4 - 1} = 27(0.1)^{3} [/tex]
Fifth term
n = 5
[tex]a(5) = 27(0.1)^{5 - 1} = 27(0.1)^{4} [/tex]
Hope this helps you